First Course In Algebraic Geometry And Algebraic Varieties - Flamini, Flaminio (London : World Scientific, 2023)
This book aims to provide insights on the latest developments in Financial Technology (FinTech). It is a collection of scientific articles covering the primary areas of finance. The following key themes are covered in the book: Machine Learning and Artificial Intelligence, FinTech Regulation and Smart Contracts, Cryptocurrencies, and FinTech in Financial Services. FinTech is a rapidly developing industry that uses technological innovations to improve financial activities and make financial services more accessible and affordable to businesses and individuals. This book contributes to the body of knowledge in FinTech, offering readers a chance to review and rethink the topics in question.
Includes bibliography and index.
Keywords: Geometry; Algebraic varieties; Polynomial rings; Homogeneous ideals